A review of recent progress on high internal-phase Pickering emulsions in food science. (December 2020) - Abdullah,; Weiss, Jochen; Ahmad, Talha; Zhang, Cen; Zhang, Hui
Abstract: Background: Interest in high internal-phase emulsions, a type of highly concentrated emulsion system, has rapidly increased in the food industry. However, traditional stabilizers made from inorganic particles and synthetic surfactants have led to adverse health effects ( e.g ., interference with the normal gastrointestinal tract, gut microbiota, and cell toxicity), which has triggered researchers to isolate and characterize new Pickering particles from natural sources. Scope and approach: Biopolymer-based particles have been suggested as efficient stabilizers of high internal-phase Pickering emulsions to satisfy consumer demand for "all natural" products and the industrial drive to provide "clean-label" food products. In this review, the particle properties including wettability, particle size, and surface charge, which govern the formation, microstructure characterization, and rheology of highly concentrated emulsions, are highlighted. Recent progress with emphasis on different types of Pickering particles assembled from biopolymers and their use in emulsions for emerging food applications are discussed. Key findings and conclusions: High internal-phase Pickering emulsions stabilized by biopolymer-based particles have promising food applications due to their advantages of well-controlled droplet size distribution, tailored morphology and rheology, surfactant-free character, low toxicity, and superior stability against physical and chemical changes as well as environmental stresses. Pickering particles are classified into three categories: polysaccharide, protein, and complex ( e.g ., protein-protein, protein-polysaccharide, protein-polysaccharide-lipid, and protein-protein-polysaccharide) particles. Recent food applications include encapsulation and controlled release, texture design and modification, lipid oxidation reduction, and trans -fat replacement. A future perspective concerning the fabrication of biopolymer-derived particles to promote their use in highly concentrated emulsions for large-scale production is proposed. Highlights: High internal-phase Pickering emulsions have potentials in food industry. Properties of biopolymer-based particles as stabilizers are highlighted. Polysaccharide, protein, and complex Pickering particles are summarized. Emerging food applications of high internal-phase Pickering emulsions are discussed.